Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Hasil Belajar IPA pada Siswa Kelas Enam Sekolah Dasar - Nurainah; Baharuddin; Violita Amalia (Tarunateach: Journal of Elementary School, 2025)
This study aims to optimize the learning outcomes of 6th grade students in Natural Sciences (IPA) at SDN Malunda, Sasende Environment, by implementing the Jigsaw cooperative learning approach. The background of this study is the low active participation and academic achievement of students in the conventional learning process. The method used is Classroom Action Research (CAR) for two cycles, involving 13 students. Each cycle includes planning, implementation, observation, and reflection. Data collection techniques are carried out through observation, documentation, and evaluation of learning outcomes. Before the implementation of Jigsaw, only 46% of students achieved completeness. This figure increased to 85% in cycle I, and reached 100% in cycle II. In addition, student activity in groups and understanding of the material also increased. These results indicate that the Jigsaw strategy is effective in building an interactive, collaborative, and meaningful learning atmosphere.